Impact of digital transformation in teacher training models - Afonso, Ana Paula (2022)
A new reality of teaching and learning through technology is continually on the rise creating the need for governments, organizations, teachers, students, and families to adapt. Students are realizing the need to become more autonomous, parents are having to become more present, and teachers are assuming new roles in virtual education. Although this new era of education is marked by innovation at all levels, most of these changes have not been thoroughly planned or structured, thus creating a difficult experience for all the educational stakeholders. Impact of Digital Transformation in Teacher Training Models conducts a critical discussion on teacher preparedness in the digital transformation of teaching practices. It promotes practitioner reflections on the role of institutional policies, teacher digital literacy, the digital divide, and how the ongoing digital transformation of society will induce the need for a paradigm shift in teacher training models. Covering topics such as emergency remote education, emerging pedagogies, and massive open online courses, this book is an essential resource for policymakers, government officials, education administration, pre-service teachers, educators, researchers, and academicians.